Pengembangan Riset Terkini Pemanfaatan Tanaman Obat dalam Penemuan Obat Baru dan Mekanismenya dalam Pengobatan Penyakit: Pengembangan Riset Terkini Pemanfaatan Tanaman Obat dalam Penemuan Obat Baru dan Mekanismenya dalam Pengobatan Penyakit - Mustofa, Syazili; Namdes, Fitri Cyntya (CV. Jasa Sukses Abadi, 2024)
Medicinal plants are plants that have medicinal properties or uses and are used to cure and prevent various diseases. Medicinal plants, both leaves, stems and roots, are partly used by the community for traditional or alternative medicine. The use of medicinal plants has evolved from generation to generation, with knowledge being passed down from generation to generation. In its utilization, medicinal plants have good opportunities, such as they are often sold as food supplements, use by the public is increasingly popular and promises minimal side effects and has challenges that must be faced, namely the need for scientific evaluation, a long time with large capital, there is a distance between preclinical models and its applications used in clinical trials as well as the lack of clinical trial data. Many drugs developed from natural sources have had revolutionary impact in medicine, including antibiotics, antiparasitic, antimalarial, lipid control agents, immunosuppressants for organ transplantation, and anticancer drugs. Medicinal plants that have properties or uses as medicinal ingredients which are currently being researched include miswak plants, centella asiatica plants, and mangrove plants.